Effect of Environmental Education on Environmental Justice and Health Equity - A. B. Is’haq (IIARD INTERNATIONAL JOURNAL OF GEOGRAPHY AND ENVIRONMENTAL MANAGEMENT, 2026)
Environmental education has been widely recognised as a critical tool for addressing environmental challenges, promoting environmental justice, and improving public health outcomes. However, empirical evidence linking environmental education to environmental justice and health equity at the community level remains limited in Nigeria. This study examined the effect of environmental education awareness and exposure on environmental justice and health equity among residents of the Federal Capital Territory (FCT), Abuja. A descriptive survey research design was adopted, and data were collected from 225 residents across selected Area Councils using a structured questionnaire administered online via Google Forms. The instrument measured environmental education awareness and exposure, environmental health knowledge and practices, environmental justice indicators, and health equity indicators. Data were analysed using descriptive statistics, two-way analysis of variance (ANOVA), and multivariate analysis of variance (MANOVA) at the 0.05 level of significance. The findings revealed significant differences in environmental education awareness and exposure, environmental health knowledge and practices, environmental justice indicators, and health equity indicators across Area Councils, with notable interaction effects between Area Council and location. The multivariate results showed that environmental education awareness and exposure had a statistically significant effect on the combined outcomes of environmental justice and health equity. Univariate analyses further indicated that environmental education exerted a stronger influence on environmental justice than on health equity, although both effects were significant. The study concludes that environmental education plays a significant role in promoting environmental justice and advancing health equity in the FCT, Abuja, albeit unevenly across spatial contexts. It recommended the adoption of context-specific, participatory, and justice-oriented environmental education strategies to reduce environmental and health inequalities and support sustainable urban development.